2017
DOI: 10.1080/21663831.2017.1396262
|View full text |Cite
|
Sign up to set email alerts
|

Excellent corrosion resistance and hardness in Al alloys by extended solid solubility and nanocrystalline structure

Abstract: Development of ultra-high strength and corrosion-resistant aluminum (Al) alloys is demonstrated by a combination of suitable alloying elements and processing technology able to cause extended solid solubility and nanocrystalline structure. Binary Al-transition metal (M: Cr, Ni, Mo, Si, Ti, Mn, V, Nb) alloys, produced by high-energy ball milling and subsequent cold compaction, have exhibited significantly high hardness and corrosion resistance compared to any commercial Al alloy. The cyclic potentiodynamic pola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 36 publications
1
30
0
Order By: Relevance
“…With the increase in grinding (12-18 h), it is observed that the parameter continues to increase, tends to expand the crystalline network of Al, until 24 h where the parameter remains constant, suggesting that Mg has completely entered the Al lattice. The analysis of the phase quantification confirms the results of the lattice parameter, where at 6 h, the largest amount of Mg in the Al lattice [6].…”
Section: Resultssupporting
confidence: 82%
“…With the increase in grinding (12-18 h), it is observed that the parameter continues to increase, tends to expand the crystalline network of Al, until 24 h where the parameter remains constant, suggesting that Mg has completely entered the Al lattice. The analysis of the phase quantification confirms the results of the lattice parameter, where at 6 h, the largest amount of Mg in the Al lattice [6].…”
Section: Resultssupporting
confidence: 82%
“…The NaCl solution prepared by dissolving 30gm NaCl in one litre water. The specimens for the tests were cut to size 20x20x 6 mm, after which the sample surfaces were polished with emery paper starting from 120 grit down to 640 grit size [19][20][21] .…”
Section: Fabrication Of Samplesmentioning
confidence: 99%
“…The Brinell hardness test is carried out to get to know the effect of the A6061 on the composites generated (Graphite, aluminium oxide, silicon carbide and boron carbide) in matrix material. The polished specimens were tested with the HBW micro durability tester and the values are depicted and shown below in Table 1 [16][17][18][19][20][21] . here the higher percentage (5%) gives a positive sign of hardness property in the prepared sample [18][19][20][21] .…”
Section: Hardness Testmentioning
confidence: 99%
See 2 more Smart Citations